DEWS: A QGIS tool pack for the automatic selection of reference rain gauges for landslide-triggering rainfall thresholds. (April 2023) - Al-Thuwaynee, Omar F.; Melillo, Massimo; Gariano, Stefano Luigi; Park, Hyuck Jin; Kim, Sang-Wan; Lombardo, Luigi; Hader, Paulo; Mohajane, Meriame; Quevedo, Renata Pacheco; Catani, Filippo; Aydda, Ali
Abstract: Several studies on empirical rainfall thresholds for landslide occurrence depend on the measurements of nearest rain gauges to the landslides, without taking in consideration the morphological and hydrological settings of the areas. Therefore, we introduce the DEWS (Distance, Elevation, Watershed, and Slope unit) QGIS software tool, for selecting representative rain gauges, a relevant step in the definition of empirical rainfall threshold models. DEWS set with default parameter values for non-expert users. DEWS employs four filters: Distance, Elevation, Watershed, Slope unit, and requires only three data inputs (digital elevation model, landslides inventory, rain gauge locations). Reliability was tested using 223 landslides and 328 rain gauges with the CTRL-T (Calculation of Thresholds for Rainfall-induced Landslides) tool applied in South Korea. Consequently, the amount of rain gauges used was optimized and reduced by 33% using DEWS from using CTRL-T alone, while the shape of the threshold curve and uncertainty values were maintained. Highlights: H1: Measuring landslide-triggering rainfall on nearest rain gauges is not adequate. H2: DEWS is open source tool for selecting representative rain gauges. H3: DEWS is complementary to any empirical and statistical rainfall threshold model. H4: DEWS incorporates different information: Distance, Elevation, Watershed, Slope unit. H5: DEM, landslides inventory and rain gauge locations are needed as input data.